ANALISIS PUISI “KUCARI JALAN MENUJU RUMAHKU” PADA ANTOLOGI AKU BAWAKAN CINTA BUATMU KARYA CHORY MARBAWI MENGGUNAKAN PENDEKATAN OBJEKTIF - Nur Haliza Fitri; Putri Dini Rawati; Nuraini Detia Putri; Rustam Rustam; Priyanto Priyanto (Universitas Batanghari, 2022)
Analyzing literary works is a common thing to do as a process of meaning or giving meaning to literary works with aesthetic intensity; another term is concretization. Various approaches are offered, one of which is an objective approach, namely an approach that focuses on the literary work itself; this approach considers literary works autonomous. As an autonomous structure, a literary work can be understood as a rounded whole with building elements. Therefore, to understand its meaning, a literary work must be analyzed based on its structure, detached from various elements outside the structure of its significance. The poem